(untitled) (Revista Peruana de Investigación Educativa, 2024)
This study explores the learning achieved by second grade secondary school students in writing argumentative texts that was mediated by the teacher via WhatsApp through the mobile phone during the mandatory confinement by COVID 19 in Peru. The students, according to their possibilities at home, wrote in three supports: WhatsApp Messenger, paper (handwritten) and Word. The study is exploratory and descriptive. In total, a corpus of 52 argumentative texts produced by students in the second grade of secondary school was analyzed. The results show that texts written in the Word processor have a higher score in relation to texts written on paper or WhatsApp Messenger, while writing on paper (handwritten) has the lowest score. Likewise, adaptation to the communicative situation (textual type, register and textual genre) is the criterion best achieved by students in the three writing supports, while punctuation, argumentation and the formal aspects of language continue to be a challenge for students. It should be noted that the feedback was provided by group and individual WhatsApp according to the student’s learning needs.